Indonesia stock exchange: Abnormal return amid pandemic - Gunistiyo Gunistiyo; Jaka Waskito; Yuni Utami (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2021)
This study aims to reveal the behavior of investors on the Indonesia Stock Exchange (IDX) before and during (early) the COVID-19 pandemic. This study is an extension of references to understand market reactions in response to future crises. This study is an event study with a time window of 76 trading days before and after the first case was officially announced by the authorities in Indonesia. Taking a sample of stocks included in the Liquid Index (LQ) 45, this study measures the abnormal return and transaction volume during the pre and post-first official announced cases and test the whole data by t-test. The results of data analysis indicate that there is no difference in abnormal returns, but there is a significant difference in transaction volume. These findings indicate that, in general, the Indonesian market is quite efficient, as evident from the absence of different abnormal returns. On the other hand, the market also appears to be cautious in making investment decisions amid uncertainty.